Forty years of foreign trade : a statistical handbook with special reference to primary products and under-developed countries - Yates, P. Lamartine (London : Allen & Unwin, 1959)
The book presents for selected years the commodity composition of world trade in value terms and to measure various kinds of changes that have occurred.
Review of data for 1913-1953.
Bibliographical footnotes.
II 17/01/2019
Loans
Keywords: Commercial statistics